Factibilidad de producto a partir de aceites de cocina usados (ACUs) (2021)
Over the past century, the deterioration of planet Earth has been quite noticeable, so several countries around the world have taken steps to reduce that impact; but not only the rulers but also, natural people have been more consenting to the daily damage they cause to the environment. This is why over the years different product proposals have been researched and implemented, whether existing or in such new cases; In addition, models of production processes have been modified; both in order to reduce pollution and consequently the impact on the environment. The work presented below is developed in order to show alternative products from used kitchen oils (ACUs) that can be used in the Colombian industry in order to expand the market, obtain environmentally friendly products and be a profitable product in that region.